2005
DOI: 10.1523/jneurosci.1886-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Position, Direction of Movement, and Speed Tuning of Cerebellar Purkinje Cells during Circular Manual Tracking in Monkey

Abstract: The cerebellum plays an essential role in pursuit tracking with the eye and with the hand. During smooth pursuit eye movements, both tracking position and velocity are signaled by Purkinje cells. Purkinje cell simple spike discharge is also modulated by direction and speed during linear manual tracking. This study evaluated how all three parameters, position, movement direction, and speed, are signaled in the simple spike discharge of Purkinje cells during circular manual tracking. Three rhesus monkeys interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
125
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(143 citation statements)
references
References 56 publications
(95 reference statements)
16
125
2
Order By: Relevance
“…For instance, by using such a mechanism, the overall integration time of gain fields would be reduced drastically and thus would result in more efficient sensorimotor transformations. Moreover, neurons having a preferential tuning to position and velocity like those of our model have been found in the cerebellum (Roitman et al 2005), a brain area suggested to be involved in both the inverse and forward control of movements (Miall and Reckess 2002;Vercher and Gauthier 1988;Wolpert and Kawato 1998). Therefore, in addition to the suggested role of neurons of the cerebellum and of motor cortices in the direct control of movements (Georgopoulos 1996;Schweigenhofer et al 1998;Todorov 2000), their sensitivity to nonlinear mixtures of information, such as arm position and velocity, may also suggest an intrinsic dynamic process within a cortical column.…”
Section: Sensorimotor Transformations and Motor Controlsupporting
confidence: 63%
See 4 more Smart Citations
“…For instance, by using such a mechanism, the overall integration time of gain fields would be reduced drastically and thus would result in more efficient sensorimotor transformations. Moreover, neurons having a preferential tuning to position and velocity like those of our model have been found in the cerebellum (Roitman et al 2005), a brain area suggested to be involved in both the inverse and forward control of movements (Miall and Reckess 2002;Vercher and Gauthier 1988;Wolpert and Kawato 1998). Therefore, in addition to the suggested role of neurons of the cerebellum and of motor cortices in the direct control of movements (Georgopoulos 1996;Schweigenhofer et al 1998;Todorov 2000), their sensitivity to nonlinear mixtures of information, such as arm position and velocity, may also suggest an intrinsic dynamic process within a cortical column.…”
Section: Sensorimotor Transformations and Motor Controlsupporting
confidence: 63%
“…Neurophysiological findings also indicate that large groups of neurons in the cerebellum display a preferential tuning to arm position and movement direction. These neurons also fire with almost no latency when compared to real arm dynamics (Fu et al 1997;Roitman et al 2005). Together, these results highly suggest that the brain may use internal forward models in order to predict the consequences of upcoming movements.…”
Section: Sensorimotor Transformations and Motor Controlmentioning
confidence: 87%
See 3 more Smart Citations